Post UMNO-BN era: electoral authoritarianism and the change of regime in Malaysia - Fong, John Wai Kinn; Teh, Benny Cheng Guan (Penerbit Universiti Kebangsaan Malaysia, 2020)
This paper aims to examine regime change in Malaysia post-GE14. It employs the notion of electoral authoritarianism to understand the importance of elections in legitimizing authoritarian rule. As the UMNO-BN regime employed higher levels of electoral authoritarianism over the years, the people began to put pressure on the regime by demanding for greater accountability, transparency and inclusivity. The outcome of the 14th General Election demonstrated the people’s power and was a crucial first step in restoring the democratic system and ending the political dominance of the UMNO-BN. Yet, more recent political developments in the country, amid Covid-19 pandemic, have raised the concerns of how fragile the situation of regime change is. Based on a qualitative method and analyses from in-depth interviews, this paper argues that while regime change was unexpectedly short-lived, the power exercised by the electorates in the GE-14 has not only substantially weakened the once dominant UMNO-BN coalition but also indirectly contributed to new political partnerships and manoeuvrings in an attempt to remain relevant.